Buffer Zones as a means to protect and conserve protected areas in developing countries - Lasso, Stud. Silv. Peter (Royal Veterinary and Agricultural University, 1995)
This thesis investigates the possible use of buffer zones as a means to protect various kinds of protected areas in developing countries. Three approaches have been applied: Ecological, socio-economic and political (political buffer zones and political buffering) protection functions of buffer zones. In addition, it is imperative that buffer zone design and implementation is carried out in cooperation with and for the benefit of local people.